LEARNING PHONEME IDENTIFICATION USING READING ALOUD TECHNIQUE: EFL LEARNERS’ PERCEPTION - Latifah, Rima; Apsari, Yanuarti (IKIP Siliwangi, 2024)
This research proposed to figure out about students’ perception in learning phoneme identification using reading aloud. The research is a descriptive qualitative research. The research involved 17 students as the respondents. The researchers utilized questionnaires and interview in collecting the data. The results of this research revealed that most of the respondents (76.47%) had positive responses toward the use of reading aloud. The data from interview also revealed several benefits that the students obtained after learning by using Reading aloud such as having new knowledge in pronunciang each phoneme properly, reading aloud offers not only joyful but also enthusiasm booster in learning, by reading aloud, students can identify their own mispronunciation, and reading aloud has an imitation method which help students in sharping students’ oral-fluency.